2022
DOI: 10.3389/fmed.2022.919708
|View full text |Cite
|
Sign up to set email alerts
|

Non-effectiveness of Ivermectin on Inpatients and Outpatients With COVID-19; Results of Two Randomized, Double-Blinded, Placebo-Controlled Clinical Trials

Abstract: BackgroundIvermectin which was widely considered as a potential treatment for COVID-19, showed uncertain clinical benefit in many clinical trials. Performing large-scale clinical trials to evaluate the effectiveness of this drug in the midst of the pandemic, while difficult, has been urgently needed.MethodsWe performed two large multicenter randomized, double-blind, placebo-controlled clinical trials evaluating the effectiveness of ivermectin in treating inpatients and outpatients with COVID-19 infection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Additionally, 15 repurposed drugs tested in 23 outpatient RCTs were included in our analysis for context: metformin 13 , fluvoxamine 13, 34, 35 , ivermectin 13, 36, 37, 38 , hydroxychloroquine 33, 39, 40, 41, 42 , nitazoxanide 43 , colchicine 44 , niclosamide 45 , four antithrombotics-aspirin, apixaban 46 , sulodexide 47 , enoxaparin 48, 49 , inhaled ciclesonide 50 , the herbal mixture Saliravira 51 , azithromycin 52, 53 , and resveratrol 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 15 repurposed drugs tested in 23 outpatient RCTs were included in our analysis for context: metformin 13 , fluvoxamine 13, 34, 35 , ivermectin 13, 36, 37, 38 , hydroxychloroquine 33, 39, 40, 41, 42 , nitazoxanide 43 , colchicine 44 , niclosamide 45 , four antithrombotics-aspirin, apixaban 46 , sulodexide 47 , enoxaparin 48, 49 , inhaled ciclesonide 50 , the herbal mixture Saliravira 51 , azithromycin 52, 53 , and resveratrol 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also revealed the antiviral activity of ivermectin associated with the ability to inhibit flavivirus replication by targeting the NS3 helicase [ 61 ], block the importin alpha/beta-mediated nuclear transport of viral proteins, capable of inhibiting the replication of HIV-1 and dengue virus [ 62 ], and inhibit SARS-CoV-2 replication in vitro [ 63 ]. Currently, the possibility of using ivermectin for the prevention and treatment of inflammatory processes induced by viral diseases [ 8 , 9 , 10 , 11 , 12 , 13 ], as well as for the treatment of cancer patients [ 14 ], is being studied. We assumed that the therapeutic effect of ivermectin is associated not only with antiviral activity, but also with its effect on human innate immunity, namely, with its effect on neutrophil function.…”
Section: Discussionmentioning
confidence: 99%
“…Some case series analysis demonstrates the ability of ivermectin to alleviate disease-associated severity and recovery rate [ 10 , 11 ]. Another analysis failed to demonstrate the efficacy of ivermectin in the treatment of COVID-19 [ 12 , 13 ]. The therapeutic effect of ivermectin is highly dependent on the phase of the disease in which the patient receives the drug [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These hypotheses need to be tested and verified using animal models [ 236 ]. It should be noted that ivermectin was studied as an antiviral in multiple clinical trials of SARS-CoV-2-infected patients [ 237 239 ] and was uniformly found to not change acute outcomes such as progression to more severe disease. It is unlikely that many of the patients in these series were concurrently parasite infected as this was not a selection criterion (or prevalence assessed), so the effect of antihelminthics on Th1 versus Th2 bias in virus and parasite coinfected individuals has not yet been tested.…”
Section: Potential Long-term Effects Of Covid-19 On the Development O...mentioning
confidence: 99%